Disconnect in the hollow state: the pivotal role of organizational capacity in community-based development organizations - Fredericksen, Patricia; London, Rosanne (2000)
Partnerships between government and community-based development organizations (CBDOs) have proven to be central to long-term neighborhood revitalization in many settings. These successes, coupled with the political popularity of community-driven projects, have stimulated further reliance on this approach. Unfortunately, scant research has been done on the organizational capacity of local community-based development organizations to administer these projects. It may be that many of them do not have the capacity to do the job. This article examines elements of organizational capacity in CBDOs developing affordable housing in a United States-Mexico border community. Evidence of capacity was limited, raising serious questions about the implementation of public policy in the hollow state. In their haste to contract with not-for-profits to create affordable housing, government officials may not be considering the serious possibility that CBDOs do not have the capacity to deliver services or effectively administer projects over time. - Reproduced
Keywords: Community development